NILAI-NILAI PENDIDIKAN KARAKTER DALAM ANIMASI IBRA BERKISAH EPISODE MUKJIZAT AIR DAN RELEVANSINYA DENGAN PENDIDIKAN AGAMA ISLAM - Fithri Lutfiah; Ahmad Haromaini; Faiz Fikri Al-Fahmi (Rausyan Fikr : Jurnal Pemikiran dan Pencerahan, 2026)
ABSTRACT Character education in Islam is a lifelong process aimed at shaping individuals who are responsible, morally upright, and grounded in faith. In today’s digital era, media such as animation plays a significant role in shaping children's character, particularly within the context of Islamic Religious Education. However, not all programs offer strong educational value. The animated series Ibra Berkisah serves as a positive alternative by presenting inspirational stories rooted in Islamic history that are both entertaining and educational. The episode “Mukjizat Air” specifically conveys character values such as patience, gratitude, cooperation, and religiosity, which align with the principles of Islamic education. This qualitative study, using content analysis of scenes, dialogues, and character behavior, aims to (1) identify the character education values in the episode “Mukjizat Air”, and (2) examine their relevance to Islamic Religious Education. The findings reveal eight key values—creativity, frugality, patience, cooperation, curiosity, religiosity, gratitude, and friendliness/communication—all of which closely relate to the Islamic educational framework encompassing faith (akidah), morality (akhlak), and religious practice (syariat).   Keywords: Education, Character, Islamic Religious Education, Animation, Ibra Berkisah, Mukjizat Air